Dolutegravir twice-daily dosing in children with HIV-associated tuberculosis: a pharmacokinetic and safety study within the open-label, multicentre, randomised, non-inferiority ODYSSEY trial - Turkova, Anna; Bwakura-Dangarembizi, Mutsa F.; Kekitiinwa, Adeodata R.; Lugemwa, Abbas; Ahimbisibwe, Grace Miriam; Burger, David M. (The Lancet HIV, 2022)
Children with HIV-associated tuberculosis (TB) have few antiretroviral therapy (ART) options. We aimed to evaluate the safety and pharmacokinetics of dolutegravir twice-daily dosing in children receiving rifampicin for HIV-associated TB.